Effectiveness and Safety of Dementia Care Management in Primary Care: A Randomized Clinical Trial - Thyrian, Jochen René; Hertel, Johannes; Wucherer, Diana; Eichler, Tilly; Michalowsky, Bernhard; Dreier-Wolfgramm, Adina; Zwingmann, Ina; Kilimann, Ingo; Teipel, Stefan; Hoffmann, Wolfgang (JAMA psychiatry (Chicago, Ill.), 2017)
Dementia care management (DCM) can increase the quality of care for people with dementia. Methodologically rigorous clinical trials on DCM are lacking. To test the effectiveness and safety of DCM in the treatment and care of people with dementia living at home and caregiver burden (when available). This pragmatic, general practitioner-based, cluster-randomized intervention trial compared the intervention with care as usual at baseline and at 12-month follow-up. Simple 1:1 randomization of general practices in Germany was used. Analyses were intent to treat and per protocol. In total, 6838 patients were screened for dementia (eligibility: 70 years and older and living at home) from January 1, 2012, to March 31, 2016. Overall, 1167 (17.1%) were diagnosed as having dementia, and 634 (9.3%) provided written informed consent to participate. Dementia care management was provided for 6 months at the homes of patients with dementia. Dementia care management is a model of collaborative care, defined as a complex intervention aiming to provide optimal treatment and care for patients with dementia and support caregivers using a computer-assisted assessment determining a personalized array of intervention modules and subsequent success monitoring. Dementia care management was targeted at the individual patient level and was conducted by 6 study nurses with dementia care-specific qualifications. Quality of life, caregiver burden, behavioral and psychological symptoms of dementia, pharmacotherapy with antidementia drugs, and use of potentially inappropriate medication. The mean age of 634 patients was 80 years. A total of 407 patients received the intended treatment and were available for primary outcome measurement. Of these patients, 248 (60.9%) were women, and 204 (50.1%) lived alone. Dementia care management significantly decreased behavioral and psychological symptoms of dementia (b = -7.45; 95% CI, -11.08 to -3.81; P < .001) and caregiver burden (b = -0.50; 95% CI, -1.09 to 0.08; P = .045) compared with care as usual. Patients with dementia receiving DCM had an increased chance of receiving antidementia drug treatment (DCM, 114 of 291 [39.2%] vs care as usual, 31 of 116 [26.7%]) after 12 months (odds ratio, 1.97; 95% CI, 0.99 to 3.94; P = .03). Dementia care management significantly increased quality of life (b = 0.08; 95% CI, 0 to 0.17; P = .03) for patients not living alone but did not increase quality of life overall. There was no effect on potentially inappropriate medication (odds ratio, 1.86; 95% CI, 0.62 to 3.62; P = .97). Dementia care management provided by specifically trained nurses is an effective collaborative care model that improves relevant patient- and caregiver-related outcomes in dementia. Implementing DCM in different health care systems should become an active area of research. clinicaltrials.gov Identifier: NCT01401582.